Effects of stair case gate bias stress in IGZO/Al2O3 flexible TFTs. (September 2018) - Buonomo, M.; Wrachien, N.; Lago, N.; Cantarella, G.; Cester, A.
Abstract: In this work, we studied the impact of stair-case gate bias stress on flexible Indium-Gallium-Zinc-Oxide Thin-Film Transistors and we estimated the breakdown voltage for different channel aspect ratios. The results show that the breakdown voltage exhibits a remarkable dependence on the channel width, while exposing no or marginal dependence on the channel length. The analysis of the threshold voltage evolution shows that after an initial increase, a remarkable decrease occurs for larger bias, indicating the action of at least two charge trapping phenomena. Highlights: We estimated the breakdown voltage on TFTs with ALD Al2O3 dielectric. We show the independence of the breakdown voltage by the TFT channel length. Both positive and negative charge trapping causes the threshold voltage shift.